Expressionisme in Nederland : 1910-1930 - Boyens, Piet; Boyens, José (Zwolle : Waanders Uitgevers, 1994)
Altink, Jan ; Barlach, Ernst ; Berg, Else ; Van Den Berghe, Frits ; Van Blaaderen, Gerrit Willem ; Campendonk, Heinrich ; Cantré, Jozef ; Chabot, Hendrik ; Colnot, Arnout ; Dijkstra, Johan ; Van Dongen, Kees ; Von Essen, Hein ; Le Fauconnier, Henri ; Filarski, Dirk ; Gestel, Leo et al.
Expressionisme in Nederland 1910-1930, Singer Museum, Laren, 17 november 1994 - 19 februari 1995
boek